THE ROLE OF SMALL BUSINESS ENTITIES IN THE DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN - Mullabayev Baxtiyarjon Bulturbayevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article examines the characteristics of the formation and development of small business entities, their specific aspects, as well as the opinions of foreign scientists on small business. In addition, comments were made on government decisions and decrees on the development and improvement of entrepreneurship in Uzbekistan and their implementation. Based on this situation, the economic analyzes of the activities of small business entities operating in the Republic of Uzbekistan were carried out, and the conclusions based on the obtained results were presented.